Future-proofing$1 (BValuing Adaptability, Flexibility, Convertibility and Optionss A Cross-Disciplinary Approach - Carmichael, David G.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2020)
This book presents a unifying approach to the valuation of incorporated flexibility. Flexibility, in general terms, recognizes future uncertainty and refers to being proactive now so as to secure the future possibility of being able to adapt, convert, or generally introduce a change, if it is worthwhile to do so at the time. That is, deliberate provision is made now in order to have the ability (but not the obligation) to adapt, convert, or change in the future; this change is discretionary, and depends on future circumstances. The applications demonstrated here cover engineering, building, housing, finance, economics, contracts, general management, and project management. The examples are as follows: designing/building features in infrastructure (including buildings and houses) such that the infrastructure can be adapted in response to future changes in climate, demographics, or usage; incorporating features in contracts such that the terms and conditions can be changed in response to changing situations; purchasing rights now such that options exist to buy or sell an asset in the future; structuring a financial investment agreement so that its terms and conditions can be changed in the future; structuring project payments to provide future guarantees of revenue if needed; and designing an operation such that it can be expanded, contracted, abandoned, switched, changed, delayed, or deferred in the future. The level of required mathematics is kept at a very modest level: an undergraduate knowledge of algebra and probability is all that is required. Numerical examples, accompanied by readily understandable diagrams, illustrate the methods outlined. The formulations are kept straightforward and accessible for practitioners and academics alike.
Introduction -- A General Formulation -- Adaptable Infrastructure -- Project Delivery -- Convertible Contracts -- Real Options -- Investment -- Financial and Energy Options -- Discussion and Conclusions.
Keywords: Industrial Management; Project management; Construction industry$1 (BManagement.s; Financial engineering; Industrial Management; Project Management; Construction Management; Financial Engineering